Analysis of Stability and Required Offset with Vibration Velocity Considering Conditions of Bedrock and Explosive Charges Using the TBM and NATM Extension Blasting Method - Suk-Min Kong; Ah-Ram Kim; Yoseph Byun; Seungbo Shim; Sang-Il Choi; Seong-Won Lee (Applied Sciences, 2022)
The development of underground spaces in urban centers has attracted significant research attention. Typical excavation methods for underground spaces in urban areas include the New Austrian tunneling method (NATM) and the tunnel boring machine (TBM). The NATM is superior in terms of ease of construction and economic efficiency; however, vibration and noise are often cited as major complaints. In addition to their high initial cost, TBMs require intricate analyses of ground conditions during excavation. To overcome the disadvantages of both methods and reduce construction time, a TBM and NATM parallel excavation method has recently been investigated. In this study, the effects of blasting vibrations on the TBM, TBM backup device, and surrounding ground were examined during an NATM application for rear expansion blasting after pilot tunnel excavation using a TBM. Different rock types and powder factors were simulated, and differences in the vibration velocity according to their variations were predicted using 3D numerical analysis.